Measurement accuracy enhancement using an optical probe system for electrically small MIMO antennas. Issue 2 (21st December 2012) - Chung, Jae‐Young; Hong, Wonbin
Abstract Well‐known measurement inaccuracy issues for electrically small multiple‐input–multiple‐output (MIMO) antennas incurred by conventional metallic cable and feed effects are mitigated by adopting an optical probe based measurement method.To demonstrate this, a closely packed MIMO antenna consisting of a pair of spirally wound antenna elements is designed and characterized using both the metallic cable feeding and the optical probe feeding methods. The measured MIMO antenna parameters, such as envelope correlation, radiation efficiency, and diversity gain, ascertain significantly improved agreement with simulation, when the optical probe feeding method is used. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:238–241, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27302